2022
DOI: 10.3389/fphar.2022.1052060
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of azacytidine and venetoclax and prognostic impact of Tim-3 and galectin-9 in acute myeloid leukemia and high-risk myelodysplastic syndromes: A single-center real-life experience

Abstract: Treatment of acute myeloid leukemia (AML) and high-risk myelodysplastic syndromes (MDS) is difficult in older patients with comorbidities and high-risk disease factors. Venetoclax, the first-in-class Bcl-2 inhibitor, has proven efficacy and safety in combination with azacytidine for treatment of high-risk myeloid diseases. In this single-center real-life retrospective study, a total of 27 consecutive patients treated with azacytidine plus venetoclax were included, and clinical outcomes, hematological improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…AML and MDS are heterogenous groups of hematologic clonal malignancies characterized by a wide range of clinical, biological, phenotypic, and molecular abnormalities, that differently affect clinical outcomes 23 . Risk stratification is currently performed using the European LeukemiaNet (ELN) guidelines for AML and the International Prognostic Scoring System‐Revised (IPSS‐R) or the novel Molecular‐IPSS (IPSS‐M) for MDS risk stratification 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…AML and MDS are heterogenous groups of hematologic clonal malignancies characterized by a wide range of clinical, biological, phenotypic, and molecular abnormalities, that differently affect clinical outcomes 23 . Risk stratification is currently performed using the European LeukemiaNet (ELN) guidelines for AML and the International Prognostic Scoring System‐Revised (IPSS‐R) or the novel Molecular‐IPSS (IPSS‐M) for MDS risk stratification 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…AML and MDS are heterogenous groups of hematologic clonal malignancies characterized by a wide range of clinical, biological, phenotypic, and molecular abnormalities, that differently affect clinical outcomes. 23 Risk stratification is currently performed using the European LeukemiaNet (ELN) guidelines for AML and the International Prognostic Scoring System-Revised (IPSS-R) or the novel Molecular-IPSS (IPSS-M) for MDS risk stratification. 25,26 Introduction of molecular alterations in MDS prognostic scoring system has represented a breakthrough in risk stratification, as molecular markers are essential disease prognosticators and can be also pharmacologically targeted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, TIM-3 inhibition may lead to different outcomes in AML compared to other leukemia. Some clinical trials have shown that TIM-3 blockade alone fails to achieve clinical efficacy for most patients with AML or MDS and improvement in clinical outcome is only observed when TIM-3 is combined with other checkpoint inhibitors, such as tyrosine kinase inhibitors (TKIs) or hypomethylating agents (HMA) [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%